Que sont les réalités de l’assurance devenues ? - Moreau, Rémi (Assurances, 1990)
What does insurance law face today? The author explains his own view on clauses set out in Civil Code, on some doctrinal misinterpretations, on proposed changes in the Quebec draft legislation and on some Courts' decisions which could be inconsistent with the insurance realities.